What are the Risk Factors for Cerebrovascular Accidents After Elective Orthopaedic Surgery?. Issue 3 (March 2016) - Minhas, Shobhit V.; Goyal, Preeya; Patel, Alpesh A.
Abstract: Background: Perioperative cerebrovascular accidents (CVAs) are one of the leading causes of patient morbidity, mortality, and medical costs. However, little is known regarding the rates of these events and risk factors for CVA after elective orthopaedic surgery. Questions/purposes: Our goals were to (1) establish the national, baseline proportion of patients experiencing a 30‐day CVA and the timing of CVA; and (2) determine independent risk factors for 30‐day CVA rates after common elective orthopaedic procedures. Methods: Patients undergoing elective TKA, THA, posterior or posterolateral lumbar fusion, anterior cervical discectomy and fusion, and total shoulder arthroplasty, from 2006 to 2012, were identified from the American College of Surgeons National Surgical Quality Improvement Program ® database. A total of 42, 150 patients met inclusion criteria. Thirty‐day CVA rates were recorded for each procedure, and patients were assessed for characteristics associated with CVA through univariate analysis. Multivariate regression models were created to identify independent risk factors for CVA. Results: A total of 55 (0.13%) patients experienced a CVA within 30 days of the procedure, occurring a median of 2 days after surgery (range, 1‐30 days) with 0.08% of patients experiencing a CVA after TKA, 0.15% after THA, 0.00% after single‐level anterior cervical discectomy and fusion, 0.38% after multilevel anterior cervical discectomy and fusions, 0.20% after single‐level posterior or posterolateral lumbar fusion, 0.70% after multilevel posterior or posterolateral lumbar fusion, and 0.22% after total shoulder arthroplasty. Independent risk factors for CVA included age of 75 years or older (odds ratio [OR], 2.50; 95% CI, 1.44‐4.35; p = 0.001), insulin‐dependent diabetes mellitus (OR, 3.08; CI, 1.47‐6.45; p = 0.003), hypertension (OR, 2.71; CI, 1.19‐6.13; p = 0.017), history of transient ischemic attack (OR, 2.83; CI, 1.24‐6.45; p = 0.013), dyspnea (OR, 2.51; CI, 1.30‐4.86; p = 0.006), chronic obstructive pulmonary disease (OR, 2.33; CI, 1.06‐5.13; p = 0.036), and operative time of 180 minutes or greater (OR, 3.25; CI 1.60‐6.60; p = 0.001). Conclusions: Numerous nonmodifiable patient comorbidities and increased operative time were associated with CVA after elective orthopaedic procedures. However, the American College of Surgeons National Surgical Quality Improvement Program ® database does not code for cardiac arrhythmia or atrial fibrillation, which other studies have suggested may be important predictor variables; those may be important risk factors, although we were unable to evaluate them in our study. Surgeons should counsel patients with these risk factors and limit their operative time to reduce the risk of these adverse events, and future studies should examine other patient characteristics such as arrhythmia and noncoronary heart disease and assess the role of pharmacologic prophylaxis in patients with these risk factors. Level of Evidence: Level III, prognostic study.